Irritable bowel syndrome - from etiopathogenesis to therapy - Radovanovic-Dinic, Biljana; Tesic-Rajkovic, Snezana; Grgov, Sasa; Petrovic, Gordana; Zivkovic, Valentina (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2018)
Irritable bowel syndrome (IBS) is a chronic and relapsing functional gastrointestinal disorder that affects 9-23% of the population across the world. Patients with IBS are often referred to gastroenterology, undergo various investigations, take various medicines, take time off work and have a poor quality of life. The pathophysiology of IBS is not yet completely understood and seems to be multifactorial. Many pathogenetic factors, in various combinations, and not all necessarily present in each patient, can play an important role. Discomfort or abdominal pain relieived by defacation, asociated with a change in stool form, is a typical clinical manifestation of IBS. Many factors, such as emotional stress and eating, may exacerbate the symptoms. A timely diagnosis of IBS is important so that treatment which will provide adequate symptomatic relief (diarrhoea, constipation, pain and boaring) can be introduced. The diagnosis of IBS is not confirmed by a specific test or structural abnormality. It is made using criteria based on clinical symptoms such as Rome criteria, unless the symptoms are thought to be atypical. Today the Rome Criteria IV is the current gold-standard for the diagnoses of IBS. Treatment of patients with IBS requires a multidisciplinary approach. Some patients respond well to non-pharmacological treatment, while others also require pharmacological treatment. This review will provide a summary of pathophysiology, diagnostic criteria and therapies for IBS.
Keywords: fekální transplantace; parasympatolytika; therapy; Humans; irritable bowel syndrome; Diet; Irritable Bowel Syndrome; Quality of Life; prevalence; chování snižující riziko; rizikové faktory; Risk Reduction Behavior; Patient Education as Topic; lidé; kvalita života; Stress, Psychological; Laxatives; Practice Guidelines as Topic; Rome criteria; dieta; genetická predispozice k nemoci; Genetic Predisposition to Disease; směrnice pro lékařskou praxi jako téma; psychický stres; Parasympatholytics; probiotika; syndrom dráždivého tračníku; Fecal Microbiota Transplantation; Prevalence; vzdělávání pacientů jako téma; Exercise; cvičení; pathogenesis; Probiotics; diagnosis; projímadla; Risk Factors